Digital Transformation in the Classroom: The Impact of Smartphone Use on Economics Learning Among 11th-Grade Students - Fatriani, Emilia; Jamiluddin, Jamiluddin; Hidayanti, Iva (Jurnal Profesi Keguruan, 2025)
This study aims to examine 1) the positive impact of smartphone usage on the economics learning process among 11th-grade students at SMAN 2 Gerung for the 2023/2024 academic year and 2) the negative impact of smartphone usage on the economics learning process among 11th-grade students at SMAN 2 Gerung for the 2023/2024 academic year. The researcher employs a qualitative approach and descriptive research type to provide a clear picture of the situation under investigation, thereby obtaining the facts. Primary and secondary data sources complement this approach. Data collection techniques include observation, semi-structured interviews, and documentation. The research findings indicate that using smartphones in learning positively impacts students. First, students have broader access to various sources of information, including scientific articles, educational videos, and digital learning platforms. Second, technology makes it easier for students to complete school assignments, as they can quickly find the references they need. Third, technology has also been proven to increase students' engagement and motivation in learning, offering more interactive and engaging learning methods. Fourth, learning becomes more flexible, allowing students to study anytime and anywhere based on their needs and convenience. However, there are also negative impacts that must be considered. Technology can disrupt students' concentration due to distractions from social media and other digital entertainment. In addition, students often struggle to distinguish between accurate and inaccurate information. They also tend to rely heavily on the internet, which can hinder the development of critical thinking and independent learning skills. Another issue is the habit of not taking complete notes, as students assume that all information is available online. Lastly, there are potential physical health concerns, such as eye strain and poor posture, caused by prolonged use of electronic devices.